Socio-demographic disadvantage and distant summary stage of cancer at diagnosis—A population-based study in New South Wales. (February 2016) - Tervonen, Hanna E.; Walton, Richard; Roder, David; You, Hui; Morrell, Stephen; Baker, Deborah; Aranda, Sanchia
Highlights: Living in socio-economically disadvantaged areas and being born outside Australia were associated with being diagnosed with distant stage cancer. Cases living in inner and outer regional areas were less likely to be diagnosed with distant stage cancer. Odds of distant stage increased over time for those living in socio-economically disadvantaged areas. In site-specific analyses, living in socio-economically disadvantaged areas was generally the strongest predictor of distant stage cancer. Abstract: Background: Past studies generally indicate that socio-demographic disadvantage is associated with lower cancer survival but evidence of an association with stage of cancer at diagnosis has been less consistent. This study examines the associations between distant summary stage and remoteness, socio-economic status and country of birth in New South Wales for invasive cancers overall and by cancer site. Methods: The population-based New South Wales Central Cancer Registry was used to obtain data on all cases diagnosed in 1980–2009 ( n = 699, 382). Logistic regression models were used to compute odds ratios (ORs) with 95% confidence intervals (CIs) for odds of distant summary stage at diagnosis. Results: A higher likelihood of being diagnosed with distant cancer was detected for those living in the most socio-economically disadvantaged areas compared with the least disadvantaged areas (OR 1.27, 95% CI 1.24–1.30) and for those born in other English and non-English speaking countries compared with Australian-born (OR 1.10, 95% CI 1.07–1.12 and OR 1.12, 95% CI 1.10–1.14, respectively) after adjusting for age, sex, diagnostic period, remoteness, socio-economic status and country of birth. Cases living in inner (OR 0.90, 95% CI 0.88–0.91) and outer regional (OR 0.92, 95% CI 0.89–0.94) areas were less likely to be diagnosed with distant stage than cases living in major cities. Odds of distant stage increased over time for those living in socio-economically disadvantaged areas. In cancer site-specific analyses, living in socio-economically disadvantaged areas was generally a stronger predictor of distant stage than remoteness or country of birth. Conclusion: Our results highlight the importance of lower socio-economic status as a predictor of distant stage at diagnosis. Socio-demographic disadvantage patterns varied for specific cancers, but in general, policy actions are recommended that emphasize earlier detection of cancers in people from lower socio-economic areas.